2005
DOI: 10.1159/000087477
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Laminin-5 γ<sub>2</sub> Chain and Epidermal Growth Factor Receptor Expression in Esophageal Squamous Cell Carcinomas

Abstract: Objectives: Laminin-5 γ2 chain (LN-5 γ2) is an extracellular matrix protein that plays an important role in cell migration and tumor invasion. We evaluated the association of LN-5 γ2 and epidermal growth factor receptor (EGFR) expression in esophageal squamous cell carcinoma (SCC). Methods: LN-5 γ2 and EGFR expression was evaluated in 110 esophageal SCC patients by immunohistochemistry, and was confirmed using esophageal SCC cell lines by Western blot analysis. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 78 publications
2
25
1
Order By: Relevance
“…This result was consistent with previous reports about ESCC (Yamamoto et al, 2001;Fukai et al, 2005) and suggested that laminin-332 at the invasive front of ESCC might have an important role in the process of tumour invasion. Laminin-332 has been reported to have potent cell migrationpromoting activity.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result was consistent with previous reports about ESCC (Yamamoto et al, 2001;Fukai et al, 2005) and suggested that laminin-332 at the invasive front of ESCC might have an important role in the process of tumour invasion. Laminin-332 has been reported to have potent cell migrationpromoting activity.…”
Section: Discussionsupporting
confidence: 93%
“…Sections with immunohistochemical staining in 430% of carcinoma cells at the invasive front were judged to be positive for laminin-332 as with the previous reports (Yamamoto et al, 2001;Fukai et al, 2005). The staining assessment was independently carried out by two of the authors (KI and YB) without any knowledge of either the clinical or survival data.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Laminin-5, which consists of a3, b3, and c2 chains, is localized in epithelial basement membranes, functions as a ligand for integrins, and plays an important role in cell migration and adhesion [15,16]. Some studies have reported that laminin c2 is expressed at the invasive front in tumor cells, while others demonstrated that loss of laminin c2 in the epithelium-stroma interface is an immunohistochemical marker of malignancy in epithelial lesions [17][18][19][20][21]. Laminin c2 expression patterns are divided into two distinct types, cytoplasmic staining and extracellular staining.…”
Section: Introductionmentioning
confidence: 99%